Un marco para la promoción de cooperativas en el contexto de planes de desarrollo territorial de regiones desfavorecidas - Coque Martínez, Jorge (REVESCO. Revista de Estudios Cooperativos, 2007)
This article proposes a framework in order to guide co-operative promotion programs in disadvantaged regions, based on understanding these enterprises as essentially participatory. Strategic Management and Participatory Research-Action elements have been combined so that they allow to structure intervention processes according to four basic spheres of analysis, decision and action: (1) selecting the barriers that limit the co-operative entrepreneurial development to have a bearing on, after diagnosing the situation of co-operatives which are the object of a certain program and its environment; (2) determining the most adequate tools of intervention in order to reduce the barriers that had been determined in the former point; (3) selecting the agents of promotion, and sharing roles among them according to their capabilities and other features which establish who is the most suitable to apply each tool; (4) continuous adjusting of the program as the promoted co-operatives are covering different phases of their life cycle.Cet article propose un cadre pour orienter des programmes de promotion de coopératives à des régions desfavorecidas, avec base à la conception de ces entreprises comme essentiellement participativas. Pour cela, se sont combinés des éléments de Direction Stratégique et d'Investigation - action Participatif qui permettent de structurer des processus d'intervention comme quatre enceintes fondamentales d'analyse, décision et comportement : (1) élection des barrières limitantes du développement patronal coopératif sur lesquelles on veut tomber, après que diagnostiquer la situation des coopératives un objectif d'un programme déterminé et celle de l'environnement de celles-ci; (2) une détermination des instruments les plus adaptés d'intervention, liés à la diminution des barrières déterminées dans le point précédent; (3) une sélection des acteurs de promotion et une distribution de papiers, en fonction de ses capacités et d'autres traits que déterminent qui est-ce qui sont plus adaptés pour appliquer des instruments déterminés; (4) une adéquation continue du programme à mesure que les coopératives provoquées parcourent différentes étapes de son cycle de vie.
Keywords: Participatory organizations; Development programs; Barriers; Tools; Agents; Life cycle; Des organisations de participation; Des programmes de développement; Des barrières; Des instruments; Les agents; Un cycle de vie